Digital Administrative Services through E-Office in the Regional Secretariat of North Sulawesi Province - Indra F. Sarundajang; Evi E. Masengi; Steven V. Tarore (JR Education, 2026)
This research analyzes the implementation of digital administrative services through E-Office in the Regional Secretariat of North Sulawesi Province. The study uses a descriptive qualitative approach to examine service capability, service optimality, user satisfaction, and determinant factors influencing digital administrative performance. Data were obtained through observation, interviews, and documentation, and analyzed through data condensation, data display, and conclusion drawing. The findings show that E-Office has improved the management of official documents, dispositions, incoming letters, and outgoing letters by making processes more orderly, faster, and more traceable. Nevertheless, the service has not yet reached optimal quality because of unstable internet connectivity, aging devices, uneven employee competence, dependence on specific operators, limited user access, delayed information updates, and inconsistent standard operating procedure implementation. Users generally feel assisted by the system, but satisfaction remains uneven because document status and completion time are not always clear. The determining factors include technological infrastructure, human resource quality, system advantages, and procedural consistency. Strengthening infrastructure, continuous training, system improvement, and procedure enforcement are required to create a more effective, efficient, transparent, and accountable digital administrative service